A criação do sistema educacional em Porto Velho entre 1940 e 1950: uma análise histórica - Geber, Andreilto Lopes (2024)
The present work aims to answer the following question: how did Brazilian educational legislation from the 1940s influence the development of the educational system in Porto Velho, and what were the actions of the federal, territorial and municipal governments that contributed to the creation and expansion of educational institutions in the region? To this end, an exploratory research methodology was adopted, based on a bibliographical review of authors specialized in regional history, in addition to the analysis of articles and official documents. The data obtained was examined using a qualitative approach, allowing a deeper understanding of the dynamics involved. The results demonstrate that, despite the scarcity of official documents on the implementation of the education system in Porto Velho, it is still possible to carry out a scientific analysis based on the information found. The few existing documents, combined with the documented political actions of the federal, territorial and municipal governments, provide a solid basis for understanding how these spheres of executive power contributed to meeting the educational demands of the local population during the period studied. The analysis reveals that government initiatives were crucial for the educational development of Porto Velho. The educational policies implemented during these years were fundamental for the creation and expansion of educational institutions, guaranteeing access to education for a growing number of children and adolescents. Cooperation between the different spheres of government was essential to overcome the region's logistical and financial challenges, allowing the construction of schools and the training of qualified teachers. Furthermore, the research highlights the importance of the Madeira-Mamoré Railway, not only as a monumental engineering work, but also as a catalyst for the urban and educational development of Porto Velho. The migration of workers and their families to the region boosted demand for public services, including education, leading the government to invest significantly in this sector. In summary, this work contributes to the understanding of educational development in Porto Velho between 1940 and 1950, elucidating the strategies and policies that allowed the expansion of the education system and highlighting the role of government actions in promoting education in the region.